Behavior of adult bottle brush weevils (Rhinostomus barbirostris) (Coleoptera: Curculionidae) - Eberhard, William G. (1983)
Several striking secondary sexual characters of the weevil Rhinostomus barbirostris serve as weapons in intraspecific battles between males for females about to oviposit. Smaller males adopt two alternative behavioral tactics in these battles which seem designed to minimize the loss in reproduction which would otherwise result from their inferior fighting abilities. Although the beetles may thus be polymorphic for fighting behavior, there was no sign of morphological dimorphisms. The sizes of their weapons (long rostra) were linearly rather than geometrically related to the sizes of other body parts. The males' behavior suggests that there is strong sperm precendence in this species.